2021
DOI: 10.1016/j.heliyon.2021.e07402
|View full text |Cite
|
Sign up to set email alerts
|

Novel starch-mediated synthesis of Au/ZnO nanocrystals and their photocatalytic properties

Abstract: A novel solution-solid synthesis method for preparation of ZnO and Au/ZnO composite nanocrystals using starch matrix has been developed and optimized. The process is characterized by simplicity, environmental compatibility and good performance. Nanocomposite samples with different gold content have been synthesized and studied with respect to their structure, size and shape of nanocrystals, thermal behavior, surface characteristics and optical properties, as well as their photocatalytic activity. We have found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Nevertheless, to date, only a few works evaluate stability, an important property for feasible applications. In order to identify the reach of our contributions, Table 2 shows the photocatalytic activity from recent works employing Au/ZnO and other nanocomposites based on ZnO as potential catalysts for wastewater remediation testing MB under UV light 24,40,41,49‐58 . As shown in the table, most of the excitation sources used by other researchers have higher power than the lamp used in this work; higher power lamps can accelerate photocatalytic mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, to date, only a few works evaluate stability, an important property for feasible applications. In order to identify the reach of our contributions, Table 2 shows the photocatalytic activity from recent works employing Au/ZnO and other nanocomposites based on ZnO as potential catalysts for wastewater remediation testing MB under UV light 24,40,41,49‐58 . As shown in the table, most of the excitation sources used by other researchers have higher power than the lamp used in this work; higher power lamps can accelerate photocatalytic mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…In order to identify the reach of our contributions, Table 2 shows the photocatalytic activity from recent works employing Au/ZnO and other nanocomposites based on ZnO as potential catalysts for wastewater remediation testing MB under UV light. 24,40,41,[49][50][51][52][53][54][55][56][57][58] As shown in the table, most of the excitation sources used by other researchers have higher power than the lamp used in this work; higher power lamps can accelerate photocatalytic mechanisms. Moreover, some works did not evaluate the photolysis (Np) that directly affects the % deg or K app reported.…”
Section: Photocatalytic Activity Of Synthesized Nanocomposites Based ...mentioning
confidence: 95%
See 1 more Smart Citation
“…In addition to its application in the production of traditional textiles, starch also has potential for the development of functional textiles, namely in functionalization with MNPs. In the green synthesis of MNPs, starch can act as a surface-capping agent; as a complexing agent to stabilize NPs, preventing their agglomeration; or as an assistant in heterogeneous nucleation [ 102 ]. Tahereh et al used starch as a capping agent in the in situ synthesis of ZnONPs on cotton fabrics.…”
Section: Polysaccharides In Metal-nanoparticle-functionalized Textilesmentioning
confidence: 99%
“…Boyan Peychev et al [ 51 ] used a novel starch-based solid solution method to prepare zinc oxide and gold-doped zinc oxide and synthesized nano-composite samples with different gold content. It was found that the nano-zinc oxide modified with gold nanocrystals had a great effect on the porosity of the nanocomposites, and the nanocomposites formed fewer micropores and mesoporous pores as shown in Figure 6 , thus reducing the specific surface area, the photocatalytic activity decreases with the increase of gold content, and the photocatalytic activity was comparable to that of pure zinc oxide when the gold content is 0.05%.…”
Section: Zinc Oxide Complex Precious Metalmentioning
confidence: 99%